A Reforma do Ensino Médio (Lei 13.415/2017) como política neoliberal para a educação básica brasileira - Rodrigues, Willians de Matos (2024)
This work is primarily aimed at examining the High School Reform (Law 13.415/2017) as an educational policy. It is an effort to understand some of the social processes that influenced the development of this reform as a public policy, considering the roles of different agents involved in educational issues during its formulation. The hypothesis in this study is that the High School Reform reflects a neoliberal conception of Education, State, and Society, and, as an educational public policy, it has concrete implications for the teaching of sociology. Therefore, it seeks to examine the foundations of Neoliberalism as a political proposal for education. It adopts a perspective that critiques neoliberalism as a normative system that produces certain types of social relations and ways of life, influencing how we are led to behave toward each other and toward ourselves. Neoliberalism, through a set of discourses, practices, and mechanisms, defines norms for social life, establishing a form of governance over people whose fundamental principle is competition. Within this framework, we are positioned in economic competition with each other and led to perceive and behave as a company (DARDOT and LAVAL, 2016). Neoliberalism, therefore, produces subjectivities. However, we seek to demonstrate how neoliberal mechanisms of subjectivity production are not detached from processes within the productive system, where productive restructuring constitutes the objective basis upon which neoliberalism develops (ANTUNES, 2017, BERNARDO, 2009, FONSECA and BRUNO, 2015, TRAGTENBERG, 1995). The research sources comprised primary documents along with a bibliographic analysis of specialized sociological texts deemed relevant to this topic, resulting in an evaluation of the High School Reform (Law 13.415/2017) grounded in the articulation of these sources with teaching practice.